Mental Toughness Atlet Remaja: Sebuah Penguatan Dukungan Implementasi Kebijakan dalam Olahraga Prestasi - Miftah Fariz Prima Putra; Untung Muhdiarto; Evi Sinaga; Sutoro Sutoro; Oscar Oswald O. Wambrauw; Fitrine Christiane Abidjulu; Samuel Piter Irab; Trajanus Laurens Jembise; Tery Wanena; Yos Wandik; Agnes Supraptiwi Rahayu; Monika Gultom; Wigati Yektiningtyas; Jhoni Jonatan Numberi; Remuz Maurens Bertho Kmurawak; Aleda Mawena; Akhmad Kadir; Rodhi Rusdianto Hidayat; Dewi Nurhidayah (Universitas Mataram, 2023)
In competitive sports, various factors influence the outcome of the game. It is believed that the mental toughness dimension is an aspect that contributes greatly to sports achievement in practice. However, unfortunately the condition of mental aspects of teenage athletes in Papua is limited explored. Therefore, the purpose of this community service was to provide assistance for the local government of Papua Province, especially the Sports and Youth Division, in providing information on the mental toughness conditions of adolescent athletes at PPLP/D Papua. The activity was carried out in three stages, namely preparation, implementation, and reporting. The results of the service found that the confidence dimension appeared to be greater than the other dimensions, while the commitment dimension was the dimension with the lowest value. For other dimensions such as positive cognition, constancy, and control were relatively in the middle. In general, the pattern of mental toughness of Papuan youth athletes appears disproportionate. Thus, mental coaching or training should provide to improve the mental quality of athletes